The Deadly Duo of COVID-19 and Cancer! - Bora, Vivek R.; Patel, Bhoomika M. (Frontiers in Molecular Biosciences, 2021)
As of 19 September 2020, about 30 million people have been infected with the novel corona virus disease 2019 (COVID-19) globally, and the no. are increasing at alarming rate. The disease has its tremendous impact on every aspect of life, but one of the humongous effects related to human health or medical sciences is Cancer disease. Nearly 2% of the total COVID-19 patients till May-2020 had cancer, the statistics are quite frightening as patient can be referred to ‘doubly unfortunate’ to suffer from cancer and to add to his misery from infection with COVID-19. Data regarding the present situation is scarce, so in this review focus is given on the deadly duo of COVID-19 and Cancer. The focus is given on molecular links between COVID-19 and cancer as inflammation, immunity and role of angiotensin converting enzyme 2 (ACE2). Complications may arise or severity may increase in cancer patients due to restrictions imposed by respective authorities as an effort to control COVID-19 and the impact may vary from patient to patient and factors may be ranging from delay in diagnosis or difficulty in management of cancer therapy as well as COVID-19 at same time, troubles in routine monitoring of cancer patients, delay in urgent surgical procedures and patient care. The effect of anti-cancer agents on the condition of cancer patient suffering from COVID-19 is discussed and whether these anti-cancer agents can be repurposed for effective COVID-19 treatment is discussed. The review will be helpful in management of deadly duo of COVID-19 and cancer.